Perceived contextual factors affecting learning strategy choice / Adelina Ebun, Hazlenah Hanafiah and Hasnawati Guliling - Ebun, Adelina; Hanafiah, Hazlenah; Guliling, Hasnawati (UiTM Press, 2016)
This study identified contextual factors that were perceived as influential in determining the learning strategy adopted by undergraduates at a higher learning institution in Sabah, Malaysia. Questionnaires were distributed to 168 students using survey items adopted from the Learning Approach model developed by Baeten et al. (2010). The data were analyzed using the statistical software, SPSS. The cross tabulation results indicated that more than 50% of the respondents adopted the deep learning strategy. It was established that "Clarity of Teaching and Learning Goals" (87.2%), "Teaching Quality" (80.1%) and "Assessment" (70.1%) were the main factors affecting students' choice of deep learning strategy. Similar results were also obtained through factor analysis, which can offer suggestions for educators and academics to consider improving the contextual factors in order to encourage university students to adopt the deep learning strategy.